Ways of Energy Supply in the Republic of Armenia - M. T. Hakobyan; A. I. Ksenofontov (Глобальная ядерная безопасность)
This article discusses the only Armenian nuclear power plant operation in Transcaucasia, the energy demand of the population of the Republic of Armenia, the restoration and secondary launch of nuclear power plants, environmental impact assessment, and prospects for the development of nuclear energy in the country. Data on personnel dose loads, emissions and discharges of nuclear power plants, soil and water pollution in the monitoring area for 2020 are presented.